La possibilité d’une géographie humaine (1961-2002) - Michel Lompech; Éric Bordessoule (Revue d’Histoire des Sciences Humaines)
Max Derruau Geography Precis was considered as one of the main popular university Geography textbooks during 50 years. The paper analyses its main characteristics and questions its exceptional longevity within academic publishing, which changing context reveals the quantitative and qualitative evolutions of higher education. Through its different republications, this textbook takes into account new questions, debates and scientific orientations of the discipline. In spite of the nowadays obsolescence of this presentation of positive knowledge in human geography, tempered by unequally achieved attempts to update the text, Derruau’s book is considered to be a classic textbook in academic human Geography.